USER STORY SOFTWARE ESTIMATION:A SIMPLIFICATION OF SOFTWARE ESTIMATION MODEL WITH DISTRIBUTED EXTREME PROGRAMMING ESTIMATION TECHNIQUE - Ridi Ferdiana; Paulus Insap Santoso; Lukito Edi Nugroho; Ahmad Ashari (JUTI: Jurnal Ilmiah Teknologi Informasi, 2011)
Software estimation is an area of software engineering concerned with the identification, classification and measurement of features of software that affect the cost of developing and sustaining computer programs [19]. Measuring the software through software estimation has purpose to know the complexity of the software, estimate the human resources, and get better visibility of execution and process model. There is a lot of software estimation that work sufficiently in certain conditions or step in software engineering for example measuring line of codes, function point, COCOMO, or use case points. This paper proposes another estimation technique called Distributed eXtreme Programming Estimation (DXP Estimation). DXP estimation provides a basic technique for the team that using eXtreme Programming method in onsite or distributed development. According to writer knowledge this is a first estimation technique that applied into agile method in eXtreme Programming.